Advances in purification technologies and applications of high-purity quartz resources - Liu, Min; Wang, Guifang; Zhao, Fanyue; Li, Wenfeng; Zhu, Gan; Liang, Guangchuan; Jian, Wei; Liao, Libing; Lv, Guocheng (Progress in natural science, 2025)
Quartz is a critical non-metallic mineral resource, with high-purity quartz sand playing a pivotal role in advanced industries such as semiconductors, solar energy, electric light sources, and special glass. In particular, 4N8-grade quartz sand (99.998 ​% purity and above) is indispensable for producing quartz crucibles, which are essential for semiconductors and solar energy applications. However, the global supply of high-quality quartz raw materials is limited, posing a challenge to meet the growing industrial demand. Furthermore, different industrial products utilize varying physicochemical properties of quartz, leading to distinct requirements for quartz raw materials and purification processes. Herein, this paper presents a comprehensive review of high-purity quartz, focusing on purification technologies and their applications. The principles, process flows, advantages and disadvantages of various purification methods are examined, with particular emphasis on chemical and physical purification techniques. The effectiveness of these methods in achieving higher purity levels and reducing impurities is critically analyzed. Furthermore, future trends in purification technologies and their potential impact on the high-purity quartz industry are discussed, offering insights for future research and applications in this field.